Effects of cerebellar transcranial direct current stimulation on improving post-stroke upper extremity motor function: a protocol for a randomized controlled clinical trial - Huang, Ziqiao; Lao, Jiahao; Chen, Zhibin; Wu, Yuxuan; Tang, Bo; Liao, Wei; Jiang, Wanqi; Liang, Junjie; Luo, Zirui; Mao, Haian (Frontiers in Neurology, 2025)
BackgroundUpper extremity motor impairment is a prevalent and disabling consequence of stroke. While conventional rehabilitation improves function, recovery often plateaus. Cerebellar transcranial direct current stimulation (c-tDCS) presents a promising neuromodulatory adjunct by targeting cerebellar involvement in motor coordination, timing, and learning. However, robust evidence from well-designed randomized controlled trials (RCTs) is needed to establish its efficacy in enhancing post-stroke upper limb recovery.ObjectiveThis RCT protocol aims to evaluate the efficacy of anodal c-tDCS applied sequentially with conventional upper limb rehabilitation (CULR), compared to sham stimulation plus the same rehabilitation, on improving motor function of the paretic upper extremity in subacute/chronic stroke patients.MethodsA double-blind, randomized, sham-controlled trial will be conducted. Fourty-eight participants with unilateral stroke and moderate to severe upper limb motor impairment will be randomized to either active or sham group. Anodal tDCS will be conducted to the ipsilesional cerebellar hemisphere in the active group, while sham delivery will be performed in the sham group. Both groups receive CULR after each c-tDCS session. Multimodal assessments will be administered pre- and post-intervention, comprising: Fugl-Meyer assessment upper extremity (FMA-UE) for motor impairment quantification, functional near-infrared spectroscopy (fNIRS) capturing resting-state and c-tDCS-induced cortical hemodynamic responses and transcranial magnetic stimulation-derived motor evoked potentials (TMS-MEPs) evaluating cortical excitability.ConclusionThis rigorously designed RCT will provide high-level evidence on the therapeutic potential of c-tDCS as an adjunct to rehabilitation for improving upper limb motor function post-stroke. Findings will inform clinical practice regarding novel neuromodulation strategies to augment recovery.Clinical trial registrationhttps://www.chictr.org.cn, identifier ChiCTR2500101094.